Wireless transfer of power to low power implanted biomedical devices: coil design considerations - Khan, Imran Moez; Khan, Sheroz; Khalifa, Othman Omran (2012)
Monolithic fabrication and advancements in MEMS and nanotechnology have made biomedical implants more popular for monitoring and other applications in humans and animals. One of the primary challenges faced in employing implants is providing a stable battery-less power supply. Inductive coupling is a commonly used means of transferring energy to implanted devices requiring power in milliwatt or microwatt range. Similar to passive RFID tags, an external transmit-coil may be used to induce a current in an implanted receive-coil by generating a magnetic field in the vicinity. However, it must be realized that the physical design of inductive coils and their orientation with respect to each other has a direct impact on the inductive link circuit, and power delivery. This paper focuses on developing three dimensional mathematical models of the magnetic field of spiral and solenoid coils to investigate the effect of lateral misalignment on the mutual inductance of the coils. Finite Element Method (FEM) simulations of the spiral and solenoid transmit coils are carried out to validate the developed models. Coil circuit parameters such as inductance, resistance and quality factor are also given.